Theoretical Frameworks of Clinical Handovers in Healthcare Settings - Lazzari, Carlo (Research Highlights in Disease and Health Research Vol. 4, 2023)
Patient handover is the pivot for transmitting patients’ information among healthcare professionals. The current study explores the theoretical frameworks supporting corporate communication and patient handover, comprising their ontology and epistemology. Clinical handover is a direct transfer of information helping the transmission of clinical notes, liability and accountability between healthcare professionals to facilitate patients’ continuity of care, shared awareness of patients’ conditions and planned management. Several theoretical frameworks support the stages of handover. According to social theories and the frameworks proposed in the current study, clinical handovers are social constructions. Handovers’ final truth and form are thus attained through constant interpersonal interactions, sharing of meanings, and distributing collective knowledge within healthcare teams. Hence, due to handover complexity, the author discusses how different professionals use social conventions to make information about patients sharable and understandable to each member of a team or other teams, and how areas of misinterpretation are always a challenge when social constructions and handovers occur.